Scientific Opinion on the safety and efficacy of L‐tryptophan produced by Escherichia coli CGMCC 7.59 for all animal species based on a dossier submitted by HELM AG on behalf of Meihua Holdings Co. Ltd. (19th February 2015) - ,; ,
Abstract: L‐Tryptophan, technically pure, is a feed additive produced by a genetically modified Escherichia coli strain (CGMCC 7.59). The additive does not give rise to safety concerns regarding the genetic modifications of the production strain. The use of L‐Tryptophan produced by E . coli CGMCC 7.59 in feed is safe for non‐ruminant target species when supplemented to diets in appropriate amounts. As the metabolites of L‐Tryptophan produced by ruminal bacteria may be toxic to the host animal, oral administration of unprotected L‐Tryptophan to ruminants should be avoided. The Panel on Additives and Products or substances used in Animal Feed (FEEDAP) has concerns about the safety of L‐Tryptophan for target species when administered via water for drinking. The composition of edible tissues and products of animal origin will not be changed by the use of the product L‐Tryptophan in animal nutrition when supplemented in appropriate amounts. No risks are expected for the consumer from the use of L‐Tryptophan, produced by E. coli CGMCC 7.59 as a feed additive, considering the purity of the additive (≥ 99.1 % L‐Tryptophan) and the low levels of 1, 1′‐ethylidene‐bis‐L‐Tryptophan (EBT) and 1‐methyl‐1, 2, 3, 4‐tetrahydro‐beta‐carboline‐3‐carboxylic acid (MTCA) (< 10 mg/kg additive each). The product L‐Tryptophan, technically pure, is considered to be non‐irritant to skin and eyes. In the absence of any data on sensitisation, the product should be considered a potential dermal sensitiser. The level of endotoxins present in the product and its dusting potential indicate a health risk for the user upon inhalation. The product under assessment does not pose any risk to the environment when supplemented to feed. The product L‐Tryptophan is regarded as an effective source of the amino acid L‐Tryptophan for all non‐ruminant species. For the supplemental L‐Tryptophan to be as efficacious in ruminants as in non‐ruminant species, it requires protection against degradation in the rumen.